Sycophantic Culture and the Sustainability of Democracy in Nigeria - Shishima, Sarwuan Daniel (International Journal of Culture and History, 2024)
Since the return to democratic or civil rule in Nigeria in 1999, we have had the opportunity to take our cherished democracy through successful successive rebirths. Our democracy has been a major factor for the changes, development and growth which we share today. This democracy has also taught us to checkmate people placed in positions in our bid to fight poverty, ensure social cohesion, facilitate the development of our social services, deepen political participation and awareness, and above all, sustain the peace of one Nigeria. However, it is observed with great concern and urgency that there is this dangerous cancerous enigmatic culture which if not tackled, has the propensity to derail and crumble our gigantic efforts to build a better Nigerian democratic culture. This cancer is what I call “sycophantic culture” which is more dangerous than the coup makers. Hence, this paper argues that this sycophantic culture in our socio-economic and political lives is one of the biggest threats we face even as we shape our democracy. Using analytic, historical and expository stencils, the paper identifies the various shades and forms this culture has hindered the making of our national rebirth where merit strives, mediocrity is shunned, ethnic cleavages are integrated at a higher level and cheap religious sentiments down played. The paper concludes using Tiv system of moral justice which reveres the pride of truth telling as a strong panacea towards building an integrative Nigerian democratic variable culture.